Accuracy of maxillary repositioning surgery using CAD/CAM customized surgical guides and fixation plates. Issue 4 (April 2021) - Wong, A.; Goonewardene, M.S.; Allan, B.P.; Mian, A.S.; Rea, A.
Abstract: The advent of three-dimensional imaging and computer-aided surgical simulation (CASS) have brought about a paradigm shift in surgical planning. The aim of this study was to assess the accuracy of maxillary repositioning surgery using computer-aided design and manufacturing (CAD/CAM) customized titanium surgical guides and fixation plates. Thirty consecutive adult patients, 13 male and 17 female, with a mean age of 29.2 years and 25.5 years, respectively, requiring Le Fort I maxillary osteotomy, with or without simultaneous mandibular surgery, were evaluated retrospectively. All orthognathic surgeries were performed by one experienced surgeon. The pre-surgical and post-surgical volumetric imaging were superimposed to assess the linear and angular differences between the planned and actual positions of the maxilla following surgery. With the use of the CAD/CAM titanium surgical guides and fixation plates, all surgical movements were within 2 mm and 4° of the planned movements, which is considered clinically insignificant. The overall root mean square error between the planned and actual surgical movements was 0.38 mm in the transverse dimension, 0.64 mm in the anteroposterior dimension, and 0.55 mm in the vertical dimension. In regard to the centroid of the maxilla, the absolute angular difference of the maxillary centroid was 1.06° in pitch, 0.47° in roll, and 0.49° in yaw. Maxillary repositioning surgery can be performed with high accuracy using CAD/CAM titanium surgical guides and fixation plates.